Opening Wedge High Tibial Osteotomy with Combined Use of Patient-Specific 3D-Printed Plates and Taylor Spatial Frame for the Treatment of Knee Osteoarthritis. (1st December 2021) - Duan, Desheng; Cao, Yang; Li, Renzeng; Wang, Guohui; Zhang, Yongfei; Xiang, Kui; Hu, Yanli; Li, Yiqun; Peng, Peng; Zhang, Pan; Liu, Xianzhe
Abstract : Background . High tibial osteotomy (HTO) is used to treat medial degeneration of the osteoarthritis (OA) knee. However, shortcomings still exist in the current procedure, like unprecise creation, inability to correct knee rotation, and internal fixed failure. Here, we reported a novel procedure: patient-specific 3D-printed plates for opening wedge high tibial osteotomy (OWHTO) combined with Taylor spatial frame (TSF). The detailed technique was described, and the clinical outcomes were evaluated. Methods . We prospectively evaluate outcomes of patient-specific 3D-printed plates for OWHTO with use of TSF in 25 patients with knee OA and varus alignment. Postoperative efficacy was evaluated using the HSS knee score, pain visual simulation score (VAS), and knee joint motion (ROM), and lower limb alignment was evaluated by measuring femorotibial angle (FTA) and hip-knee-ankle (HKA). Results and Conclusion. All patients did not experience complications such as wound infection, nerve damage, or bone amputation. 25 patients were followed up for 6–18 months. The bony union at bone amputation was achieved in 3 months after surgery, and the pain symptoms were significantly alleviated or disappeared. The VAS score was significantly reduced in 6 months after surgery compared with preoperative; the HSSS score was significantly added in 6 months after surgery compared with preoperative. The ROM of knee joint increased significantly 6 months after operation compared with that before operation, and the difference was statically significant (P < 0.05 ). The FTA and HKA after operation were significantly superior to that before operation, and the difference was statically significant (P < 0.01 ). Conclusions . Our study showed that patient-specific 3D-printed plates for HTO with the use of TSF have the advantages of small trauma, few complications, simple operation, and fast recovery in treating knee OA and varus alignment.